Exploring Language Learning Experiences of Kurdish and Turkish Asylum Claimants in Canada Through Arts-Informed Research - Palta, Zehra Melike (Journal of the Canadian Association for Curriculum Studies, 2020)
According to United Nations High Commissioner for Refugees, the highest level of displacement on record was reached in 2019 with 79.5 million people being forced to migrate (United Nations High Commissioner for Refugees, 2020). Although there is a significant influx of asylum seekers arriving in Canada from Turkey, there have been no studies completed in Canada that focus on the experiences of Kurdish and Turkish refugee claimants. Asylum seekers’ lived experiences need to be further investigated because their precarious legal status together with changing governmental policies may limit their access to language education and resettlement programs. Grounded in the arts, this paper analyzes the role of languages and language-learning experiences on Turkish and Kurdish asylum seekers and their integration into Canadian life. Participants were given the opportunity to document their challenges, needs, concerns and successes related to their integration and language-learning experiences by creating different art forms. Analysis of the data is made through the lens of Cooper’s (2011) Bridging Multiple Worlds Theory and Freire’s (1972) concept of critical consciousness. This research will be informative for educators and policy makers involved in the education of young adults from refugee backgrounds.